Effects of Game and Game-like Training on Neurocognitive Plasticity - Heleen A. Slagter (Frontiers Research Topics, 2016)
Cognitive training is not always effective. This is also the case for the form of cognitive training that this Research Topic focuses on: prolonged performance on game-like cognitive tasks. The ultimate goal of this cognitive training is to improve ecologically-valid target functions. For example, cognitive training should help children with ADHD to stay focused at school, or help older adults to manage the complexity of daily life. However, so far this goal has proven too ambitious. Transfer from trained to non-trained tasks is not even guaranteed in a laboratory, so there is a strong need for understanding how, when and for how long cognitive training has effect. Which cognitive functions are amenable to game training, for whom, and how? Are there mediating factors for success, such as motivation, attention, or age? Are the improvements real, or can they be attributed to nonspecific factors, such as outcome expectancy or demand characteristics? Are there better strategies to improve cognitive functions through game training? This Research Topic of Frontiers in Human Neuroscience charts current insights in the determinants of success of game training.